Issues pertaining to posology in ancient Greek, Roman and Byzantine medical texts - Valiakos, Elias; Marselos, Marios; Diamandopoulos, Athanasios (DELTOS, 2024)
Researching medical texts of the past reveals that the preparation of a therapeutic recipe usually involved the use of several active ingredients. There are many detailed reports on the ratio of the ingredients in a recipe, but also on the dosage administered to the patient. In this article, we recorded the use of units of weight and volume in therapeutic recipes from antiquity, the Hellenistic era, the Roman Empire, Byzantium, and also empirical medical texts of the 19th century. The changes emerging over time from the growing trade in the wider Mediterranean area, with the introduction of both new products and new units of measurement, did not affect the basic principles of the therapeutic methods. Through the centuries, the main concern of physicians was to fight the disease without burdening the patient with any unwanted effects. In this context, we observe even dosage modifications when it comes to special vulnerable population groups, such as children, the elderly and pregnant women. The period covered is very large, which means that the approach is impressionistic not aiming to the philologists. We hope that this does not pose a problem to the interested historians of medicine.